The Mozart effect on spatial-temporal reasoning skills recommendations for a musically-enhanced pre-school library - Jamin, Raymond P. (2001)
The library is an important venue in the learning process and the aim of this research is to further enhance the "learning experience" in the said venue. Music has often been believed to possess many qualities that can enhance the physical, emotional and mental capabilities and capacities of human beings.